Journal of Basic and Clinical Physiology and Pharmacology (De Gruyter, 1986)
The journal publishes novel research in the physiological and pharmacological sciences, including brain research, cardiovascular-pulmonary interactions, hematology, immune response, inflammation, metabolism, oxidative stress, and phytotherapy. It also publishes papers on cutting-edge techniques in cellular and molecular biology that link descriptive and behavioral studies with cellular and molecular mechanisms.